Case Report: Two Infant Cases of Langerhans Cell Histiocytosis Involving the Digestive Tract - Wang, Huan; Wang, Yuesheng; Wang, Ruifeng; Li, Xiaoqin (Frontiers in Pediatrics, 2021)
Langerhans cell histiocytosis (LCH) is a rare disease with uncertain etiology. LCH with involvement of the gastrointestinal tract is rare and typically identified in pediatric patients with systemic disease. Here, we report 2 infantile cases of LCH who initially presented with diarrhea, hematochezia and rash and were histologically missed on original sections of a colonic biopsy.The diagnosis of LCH were verified later with immunohistochemistry examinations. Combining our experience and reports before, multi-hemorrhagic spots of the colorectal mucosa, as well as narrowness and erosion of the distal duodenum might be a suggestive manifestation of gastrointestinal involvement in LCH in the endoscopy tests, which might be helpful for the early recognition of the disease.